Potency of Kaliasem Bark (Syzygium polychephalum) Extract as Antibacterial Agent for Staphylococcus aureus - Ni Luh Putu Agustini; Desak Putu Risky Vidika Apriyanthi; Ayu Saka Laksmita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Nosocomial infectious diseases are caused by Staphylococcus aureus bacteria. Treatment of infection can use drugs in the form of substances produced by a microorganism in the form of antibiotics. However, the problem that often arises with antibiotics is the occurrence of resistance. Alternatives that are able to overcome the problem of antibiotic resistance against bacteria are plants that have antibacterial activity, one of which is kaliasem (Syzygium polychephalum). This study aims to determine the compounds contained in the ethanol extract of the bark of kaliasem (Syzygium polychephalum) and to determine the potential of its activitiy on the growth of Staphylococcus aureus in vitro. The bark extract of kaliasem (Syzygium polychephalum) had been carried out by using maceration method. Determination of antibacterial activity was carried out by the disc diffusion method. The ethanolic extract of the bark of kaliasem (Syzygium polychephalum) contains antibacterial compounds such as tannins, phenolics, terpenoids, alkaloids and flavonoids and the ethanolic extract of the bark of kaliasem (Syzygium polychephalum) at concentrations of 25%, 50%, 75% and 100% can inhibit growth of Staphylococcus aureus bacteria with an average inhibition zone of 15.85 mm, 18.36 mm, 23.64 mm, 28.58 mm, respectively. Therefore, it can be concluded that the ethanolic extract of the bark of kaliasem (Syzygium polychephalum) contains antibacterial compounds and has the potential to inhibit the growth of Staphylococcus aureus bacteria.